Modelling for Sustainable Development Goals (SDGs) - Barbero Vignola, Giulia,Acs, Szvetlana,Borchardt, Steve,Sala, Serenella,Giuntoli, Jacopo,Smits, Paul,Marelli, Luisa (Publications Office of the European Union, 2020)
Evaluating the potential impacts of each policy on all sustainability dimensions (economic, social and environmental), as captured in the UN SDGs and their targets, requires system thinking and shifting away from single disciplinary projects towards multi- and inter- disciplinary approaches that recognize complexities and acknowledge uncertainties. Modelling is an essential tool to increase the understanding of qualitative and quantitative drivers of sustainability, contributing to the implementation of specific SDGs. The report presents the mapping of JRC models against SDGs, in order to identify links between model outputs and SDGs at target and indicator levels, and facilitate the use of models for sustainability assessment in support of EU policy making. The mapping considers 108 modelling tools listed in MIDAS, the Modelling Inventory and Knowledge Management System of the European Commission. A first analysis on the links between models and the SDG framework was carried out starting from the online description available in MIDAS. Modellers were further requested to validate the initial assessment, confirming the links identified and eventually proposing additional ones, through one survey and two workshops organised in 2019. This analysis offers a transparent mapping of how models outputs can be directly or indirectly linked to EU/UN SDGs indicators, how trade-offs and interplays can be assessed, therefore indicating to what extent JRC models can quantitatively evaluate the impacts of policy options on SDGs, targets and indicators.
10.2760/697440
Keywords: Graue Literatur; sustainable development; research method; EU policy; knowledge management; European Commission; cartography; European Union; UNO; impact study; poverty; sustainable agriculture; teaching quality; gender equality; water management; economic growth; innovation; town; consumption; cooperation policy; report